Колдунья поневоле: роман / А. Бушков - Бушков Александр Александрович (Олма Медиа Групп, 2008)
Экземпляры: ф. 4 (20100127) / Инвентарный номер: 95773 / Цена: 60 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 94 / ББК: 84(2Рос=Рус)6